2017
DOI: 10.1186/s12957-017-1175-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of liver metastasis from advanced pancreatic adenocarcinoma: a large multicenter cohort study

Abstract: BackgroundClinical prognostic parameters of liver metastasis from pancreatic adenocarcinoma have not been specifically identified.This study is to explore the risk factors of liver metastasis in advanced pancreatic adenocarcinoma (PDAC) patients in China.MethodsA multicenter cohort study was conducted to explore whether liver metastasis in locally advanced and metastatic PDAC could be reflected by some common laboratory indexes. We collected 1787 advanced PDAC patients from three participating hospitals betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Among them, pancreatic adenocarcinoma (PDAC) is the most malignant subtype with a 5-year survival rate of less than only 5% [ 5 ]. Radical operation is the only way to cure PDAC, but over 85% of patients are already at advanced stages upon initial diagnosis that has lost the chance of radical resection [ 6 8 ]. Currently, coalition therapy combining surgery with chemotherapy, radiotherapy or immunotherapy is the main option in the clinic, however, PDAC is characterized by an extraordinary resistance to chemo- and radiotherapy as well as to molecularly targeted therapy and immunotherapy [ 9 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, pancreatic adenocarcinoma (PDAC) is the most malignant subtype with a 5-year survival rate of less than only 5% [ 5 ]. Radical operation is the only way to cure PDAC, but over 85% of patients are already at advanced stages upon initial diagnosis that has lost the chance of radical resection [ 6 8 ]. Currently, coalition therapy combining surgery with chemotherapy, radiotherapy or immunotherapy is the main option in the clinic, however, PDAC is characterized by an extraordinary resistance to chemo- and radiotherapy as well as to molecularly targeted therapy and immunotherapy [ 9 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown some correlation between the clinical and pathological factors for the predisposition of liver metastasis in patients with PDAC 9,10. However, those reports were mainly based on small cohorts of patients and only evaluated fragmentary factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dong et al reported a retrospective study that included 1,787 advanced PDAC patients. 10 They demonstrated that both primary tumor location and diameter were significantly associated with the risk of synchronous liver metastasis. Tumor size, a powerful and reliable predictor of both distant metastasis and prognosis, 5,27 was found to have an intimate association with the infiltration of the pancreatic cancer cells into the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown some correlation between the clinical and pathological factors for the predisposition of liver metastasis in patients with PDAC. 9,10 However, those reports were mainly based on small cohorts of patients and only evaluated fragmentary factors. It would be interesting to study the association between clinicopathological factors and liver metastasis, and to construct effective models to predict the risk of liver metastasis for patients with PDAC.…”
Section: Introductionmentioning
confidence: 99%